Building standards of simulation reference for some physical abilities as an indicator for choosing specialized handball talented school-players between 12 and 14 years in Iraq - Bayati, Bashar Ghaleb Shihab Al; Al-Azzawi, Maha Hasan Mosleh; Al-Zuhairi, Saifuldin Watheq Fouad (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the current research in setting up a correct scientific mechanism for selecting handball players based on testing and measuring objectively instead of subjectivity in selection, by finding standard spoken reference and based on scientific foundations that help coaches get players those with a high level of physical performance thus achieving the best results. It has been concluded that the researcher standards of reference tests Research (speed transition, explosive power, flexibility), and that the test results were acceptable for the age of the research sample tests research, and recommend a researcher using this by trainers specialized schools for the gifted in the selection of handball players Reconstruction (12-14) years old in Iraq, and conducting similar studies in variables that were not addressed in the study and on other age groups.